2020
DOI: 10.1155/2020/4360930
|View full text |Cite
|
Sign up to set email alerts
|

The miR-582/CD1B Axis Is Involved in Regulation of Dendritic Cells and Is Associated with Clinical Outcomes in Advanced Lung Adenocarcinoma

Abstract: The involvement of immune dysfunction in the pathogenesis of lung cancer has been extensively studied. However, the potential molecular mechanisms through which the tumor immune response affects drug resistance are still unclear. Accordingly, in this study, we evaluated deviations in the immune cell landscape among patients with different stages of lung adenocarcinoma to identify key microRNAs and their targets associated with patient outcomes. CIBERSORT was used for estimating the proportions of immune cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…To ascertain the association of IRGs with immune in ltration, we used a marker called CD1B. Guo et al found that miR-582/CD1B, which are involved in resting and activated dendritic cells, may be potential novel biomarkers for immunotherapy (47). Similar to our study, in prostate cancer, the decreased levels of CD1B expression could be linked to the poorer disease-free survival (48).…”
Section: Discussionsupporting
confidence: 77%
“…To ascertain the association of IRGs with immune in ltration, we used a marker called CD1B. Guo et al found that miR-582/CD1B, which are involved in resting and activated dendritic cells, may be potential novel biomarkers for immunotherapy (47). Similar to our study, in prostate cancer, the decreased levels of CD1B expression could be linked to the poorer disease-free survival (48).…”
Section: Discussionsupporting
confidence: 77%
“…CD1B was signi cantly positively correlated with checkpoint molecules HAVCR2 and CTLA4 (Yuan et al, 2020). Another study showed that in LUAD, a higher CD1B expression showed signi cantly increased fractions of Resting Mast cells, Monocytes, Memory B cells, and Activated Resting Dendritic cells, but signi cantly decreased fractions of Follicular Helper T cells, Resting NK cells, M0 Macrophages, and Naive B cells (Guo et al, 2020;Pereira et al, 2019). SCGB3A1 was a signi cant independent predictor of poor clinical outcome in early-stage NSCLC (Marchetti et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To ascertain the association of IRGs with immune infiltration, we used a marker called CD1B. Guo et al found that miR-582/CD1B, which are involved in resting and activated dendritic cells, may be potential novel biomarkers for immunotherapy [ 47 ]. Similar to our study, in prostate cancer, the decreased levels of CD1B expression could be linked to the poorer disease-free survival [ 48 ].…”
Section: Discussionmentioning
confidence: 99%